2011
DOI: 10.1080/00918369.2011.614909
|View full text |Cite
|
Sign up to set email alerts
|

Motivation Factors for Participation in GLBT Sports League

Abstract: This study investigated those factors that motivate members of the GLBT (gay, lesbian, bisexual, transgender) community to participate in a GLBT sports league. Data from a survey of 1151 members of a Chicago GLBT sports association were analyzed using exploratory factor analysis to determine the variables that contributed most to explaining leisure motivation in this setting. Results showed that the intellectual and social factors were the primary factors in determining motivation in participation. Also contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Participation in recreation has also been shown to have benefits to soft skills such as time management, sense of belonging, respect for others, and academic performance (Forrester, 2014). Place and Beggs (2011) found similar health and social motivations concerning why participants join gay recreational sports leagues.…”
Section: Rsj Vol 39 No 2 2015mentioning
confidence: 72%
“…Participation in recreation has also been shown to have benefits to soft skills such as time management, sense of belonging, respect for others, and academic performance (Forrester, 2014). Place and Beggs (2011) found similar health and social motivations concerning why participants join gay recreational sports leagues.…”
Section: Rsj Vol 39 No 2 2015mentioning
confidence: 72%
“…Some of these clubs have a history of more than 25 years and participate in the regular competitions held in this country. Some of them have their origin in the need that arose on the part of LGBTQ athletes to practise sport in a climate of respect and tolerance for gender and sexual diversity (Place & Beggs, 2011); although new studies point out to a search for social capital, for example, meeting new people would be among the most relevant motivations today (Muir et al, 2020).…”
Section: Profiling a Research Object: Lgbtq Sport In The Context Of C...mentioning
confidence: 99%
“…The differences in motivations continue when various sports are considered (McDonald et al, 2002) as well as different sample groups (Frederick & Ryan, 1993;McDonald et al, 2010;Milne, & Hung, 2002;Ogles & Masters, 2000;Place & Beggs, 2011). This collection of research identifies three important findings.…”
Section: Scales and Theoretical Frameworkmentioning
confidence: 99%
“…While it has been shown that motivational distinctions exist across leisure activity activities (Frederick & Ryan, 1993;McDonald et al, 2010;Milne & Hung, 2002;Ogles & Masters, 2000;Place & Beggs, 2011;Sieppel, 2006), still some differences and similarities exist within the same activities. Of particular interest in the current study is the behavior of endurance sport participants.…”
Section: Scales and Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation